The effect of a culturally responsive teaching approach using digital comics on critical thinking skills in photosynthesis learning - Desy Fitria, Marsanda; Lestari Handayani, Sri (Universitas Ahmad Dahlan, 2025)
Learning in the 21st century highlights the need to enhance students' critical thinking abilities by incorporating information and communication technology. This study examines the effect of the Culturally Responsive Teaching (CRT) approach using digital comics on the critical thinking skills of fourth-grade students in learning about photosynthesis. The aspects of critical thinking measured include analysis, evaluation, and interpretation. This study employed a quasi-experimental design with a non-equivalent control group, involving 62 students who were assigned to either the experimental or control group. The independent samples t-test revealed a statistically significant difference between the experimental and control groups (p = 0.024), indicating that students taught using CRT-based digital comics demonstrated better critical thinking performance than those taught using conventional methods. The digital comics integrated local cultural values, such as traditional beverages, indigenous plants, and everyday community practices, making the learning process more contextual and meaningful. This study highlights the potential of CRT-based digital comics to enhance students’ cognitive skills and offers an innovative model for integrating cultural relevance into elementary science education.